Chronic Maternal Depression Is Associated with Reduced Weight Gain in Latino Infants from Birth to 2 Years of Age - Wojcicki, Janet M. (Public Library of Science, 2011)
BACKGROUND: Latino children are at increased risk for mirconutrient deficiencies and problems of overweight and obesity. Exposures in pregnancy and early postpartum may impact future growth trajectories. OBJECTIVES: To evaluate the relationship between prenatal and postnatal maternal depressive symptoms experienced in pregnancy and infant growth from birth to 2 years of age in a cohort of Latino infants. METHODS: We recruited pregnant Latina mothers at two San Francisco hospitals and followed their healthy infants to 24 months of age. At 6, 12 and 24 months of age, infants were weighed and measured. Maternal depressive symptoms were assessed prenatally and at 4-6 weeks postpartum. Women who had high depressive symptoms at both time periods were defined as having chronic depression. Logistic mixed models were applied to compare growth curves and risk for overweight and underweight based on exposure to maternal depression. RESULTS: We followed 181 infants to 24 months. At 12 and 24 months, respectively, 27.4% and 40.5% were overweight, and 5.6% and 2.2% were underweight. Exposure to chronic maternal depression was associated with underweight (OR = 12.12, 95%CI 1.86-78.78) and with reduced weight gain in the first 2 years of life (Coef = -0.48, 95% CI -0.94—0.01) compared with unexposed infants or infants exposed to episodic depression (depression at one time point). Exposure to chronic depression was also associated with reduced risk for overweight in the first 2 years of life (OR 0.28, 95%CI 0.03-0.92). CONCLUSIONS: Exposure to chronic maternal depression in the pre- and postnatal period was associated with reduced weight gain in the first two years of life and greater risk for failure to thrive, in comparison with unexposed infants or those exposed episodically. The infants of mothers with chronic depression may need additional nutritional monitoring and intervention.